2018
DOI: 10.1080/21505594.2017.1423189
|View full text |Cite
|
Sign up to set email alerts
|

The novel microtubule-associated CAP-glycine protein Cgp1 governs growth, differentiation, and virulence of Cryptococcus neoformans

Abstract: Microtubules are involved in mechanical support, cytoplasmic organization, and several cellular processes by interacting with diverse microtubule-associated proteins such as plus-end tracking proteins, motor proteins, and tubulin-folding cofactors. A number of the cytoskeleton-associated proteins (CAPs) contain the CAP-glycine-rich (CAP-Gly) domain, which is evolutionarily conserved and generally considered to bind to α-tubulin to regulate the function of microtubules. However, there has been a dearth of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Tubulin organization in C. neoformans and C. gattii was evaluated as described by Wang et al . (44) with minor modifications. Briefly, fungal cells were cultivated overnight in liquid Sabouraud medium at 30°C under shaking (200 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Tubulin organization in C. neoformans and C. gattii was evaluated as described by Wang et al . (44) with minor modifications. Briefly, fungal cells were cultivated overnight in liquid Sabouraud medium at 30°C under shaking (200 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent compelling study, Wang et al, identified a unique cytoskeleton-associated protein and examined its role in the pathogenesis of C. neoformans [ 5 ]. All eukaryotes consist of cytoskeletal filaments that include microtubules made from tubulin.…”
mentioning
confidence: 99%
“…CAP-Gly proteins have been characterized in Saccharomyces cerevisiae and in Saccharomyces pombe , however the functional activity of CAP-Gly proteins in fungal pathogens are unknown thus underscoring the relevance of the study by Wang et al The goal of the study was to identify CAP-Gly proteins in Cryptococcus neoformans and to establish whether CAP-Gly proteins mediate mechanisms of pathogenesis [ 5 ]. The authors identified five genes predicted to encode CAP-Gly domains and subsequently used an in silico approach to analyze the protein domain structure of each gene.…”
mentioning
confidence: 99%
See 2 more Smart Citations